Moderate prevalence of foot ulceration risk according to the IWGDF guidelines in type 2 diabetic patients attending the primary health care - Rodríguez Alonso, Dante (2018)
Objective: To determine the prevalence of foot ulceration risk (FUR) according to the International Working Group on the Diabetic Foot (IWGDF) guidelines, demonstrated by the presence of peripheral diabetic neuropathy (PDN) and/or peripheral arterial disease (PAD) and/or deformity (D), as well as its associated factors, in type 2 diabetic patients attending the primary health care (PHC) in Trujillo. Materials and methods: A sample of 301 type 2 diabetic patients was collected from public and private health centers of the district of Trujillo belonging to the PHC. Subsequently, said sample was stratified according to the IWGDF guidelines on foot at risk, considering diagnoses such as PDN, PAD and D. Descriptive and analytical statistics were performed with the variables evaluated by the IBM SPSS Statistics V22.0. In addition, accreditation was requested from an ethics and research committee. Results: Type 2 diabetic patients showed the following diagnoses: 13.3 % presented PDN, 18.6 % PAD and 64.1 % D. Besides, it was found that 86.7 % have no FUR, 4 % are at slight risk of and 9.3 % are at moderate risk of developing foot ulcers, with a total prevalence of 13.3 %. Finally, the associated risk factors were medical attention frequency, hypertension, hypoglycemia, physical activity and orthopedic footwear. Conclusions: This is the only epidemiological study performed in the Peruvian PHC showing a moderate prevalence of FUR, but lower than its Latin-American peers’ experiences. Deformity was the most frequent component, and positive and very weak associated factors were found when analyzing patients with and without risk factors.